Growth and Yield Performance of Foxtail Millets Under Salinity - Nahar, A; Mannan, MA; Mamun, MAA; Ghosh, TK (Bangladesh Agronomy Journal, 2018)
Crop diversification in saline affected coastal areas is crucial for food security in Bangladesh. A pot experiment was conducted at polythene house at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur-1706 during May to August, 2017 to determine the effect of salt stress on growth and yield performance of foxtail millets. Five foxtail millets genotypes viz. (i) BARI Kaon-1 (check), (ii) BD-878, (iii) BD-897, (iv) BD-891 and (v) BD-881 were tested under three salt stresses viz. (i) control (0 dS/m), (ii) 6 dS/m and (iii) 12 dS/m. Completely randomized design (CRD) with three replications was followed in the study. The growth parameter viz. stem dry matter, leaf dry matter and root dry matter production of foxtail millets genotypes were significantly varied due to salinity stresses. Salinity stresses also significantly influenced yield and yield contributing characteristics of foxtail millets. The genotypes BD-897 and BD-881 produced the higher dry matter, grains per panicle and grain yield per plants under the saline level of 6 dS/m. The higher stress tolerance index of both the genotypes demonstrate that the genotypes BD-897 and BD-881 were more salt tolerant. Bangladesh Agron. J. 2018, 21(1): 51-59